ANALISIS FAKTOR-FAKTOR INDIVIDUAL DALAM PENGAMBILAN KEPUTUSAN ETIS OLEH KONSULTAN PAJAK - Pitaloka, Frigasari Dianing; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the influence of Machiavellian characteristics, perception of the importance of ethic, and social responsibility, ethics consideration, and risk preference to the ethics decision making which has been made by tax consultants which are listed as the member of the Indonesia Tax Consultant Association (IKPI) branch Surabaya. This research has been carried out by using multiple linear regressions analysis. The data collection method has been conducted by using questionnaire which is delivered through personal email to the tax consultant. The samples are 78 tax consultant which has been listed become a members in of Indonesia Tax Consultant Association (IKPI) Surabaya branch. The hypothesis test has been carried out by using regressions analysis with the instrument program of SPSS. The result of this research shows that the Machiavellian characteristics and risk preference give any significant and negative influence to the ethical decision making. It means that when the tendency of Machiavellian characteristics and risk preference is low, so the decision making is more ethical. Meanwhile the importance of ethical perception and social responsibility give significant and positive influence to the ethical decision making. As well as the ethical consideration give significant and positive influence to the ethical decision making. The result of determination coefficient test shows that simultaneously give influence is 30,4% to the ethical decision making.Keywords: Machiavellian, social responsibility, ethical consideration, risk preference, ethical decision making